Addressing Power in Conversation: Enhancing the Transformative Learning Capacities of the World Café. (July 2016) - Lorenzetti, Liza A.; Azulai, Anna; Walsh, Christine A.
The World Café (TWC), used as an effective conversational tool around the world, shares several tenets with other participatory approaches to learning and development. It has not been critiqued, however, for its insufficient attention to reflexivity, power differentials, and structural inequalities within its process, specifically in relation to TWC facilitators. As a group of women from diverse social locations and backgrounds committed to the pursuit of social justice, we sought this opportunity to explore and investigate the transformative learning capacities of TWC, with the broader goal of enhancing its usability in education and community settings. We reviewed and critiqued TWC conversation approach, suggesting stronger links to liberatory education and transformative learning theories. Using a participatory action research process leading to cocreated knowledge, we developed an Emancipatory Learning Charter, a new tool that can enhance the transformative learning potential of TWC.